2001
DOI: 10.1007/s004420000536
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of diversity: maintenance of species richness in changing environments

Abstract: In order to assess how diversity changes over time at sites undergoing environmental change, we examined three data sets on long-term trends in taxonomic richness and composition: (1) 22 years of rodent censuses from a site in the Chihuahuan Desert of Arizona; (2) 50 years of bird surveys from a three-county region of northern Michigan; and (3) approximately 10,000 years of pollen records from two sites in Europe. In all three cases, richness has remained remarkably constant despite large changes in compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
236
1
9

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(258 citation statements)
references
References 77 publications
(68 reference statements)
12
236
1
9
Order By: Relevance
“…Diversity Dynamics Through Time. A growing body of work has demonstrated that environmental variability affects species diversity on short time scales (33,101,102), suggesting a species-time relationship (103) as an analog to the species-area relationship. However, key differences between spatial and temporal processes imply that they may have unique diversity-scaling relationships (103,104).…”
Section: Spanning the Missing Middlementioning
confidence: 99%
See 1 more Smart Citation
“…Diversity Dynamics Through Time. A growing body of work has demonstrated that environmental variability affects species diversity on short time scales (33,101,102), suggesting a species-time relationship (103) as an analog to the species-area relationship. However, key differences between spatial and temporal processes imply that they may have unique diversity-scaling relationships (103,104).…”
Section: Spanning the Missing Middlementioning
confidence: 99%
“…Brown et al (102) examined how environmental variability may regulate diversity dynamics in several systems, including Holocene fossil pollen records at family resolution. They postulated that although environmental change maintains diversity by influencing colonization and extinction of different species, when sufficiently large it could alter diversity by changing species-level carrying capacity (102). These conjectures remain unexplored.…”
Section: Spanning the Missing Middlementioning
confidence: 99%
“…S; it stands for all the species in a plot; S is the number of species; N is the sum of the numbers of all species in a plot; ni is the number of ith species in a plot; c is the number of species that appear in both a plot and control area; a and b are the number of species that appear in the plot and the control, respectively. Previous studies have shown that human disturbance has little influence on, or even helps keep high diversity levels (as shown with increases in the SHDI after disturbance events) (Brown, Ernest, Parody, & Haskell, 2001;Schnoor & Olsson, 2010;Gourlet-Fleury et al, 2013). Consequently, the situation of vegetation recovery cannot be evaluated solely by SHDI.…”
Section: Data Acquisition and Processingmentioning
confidence: 99%
“…Recent theoretical advances indicate that biodiversity as a phenomenon may affect ecosystem functions such as productivity and resilience (e.g., species richness and composition; see Tilman et al 1996;Yachi and Loreau 1999;Tilman 2000Tilman , 2001Kennedy et al 2002;Bond and Chase 2002;Loreau et al 2003). Moreover, in some places assemblages of several groups were stable through time (see Brown et al 2001;; even through the dramatic Holocene climate changes (see Rodríguez 2004). In this context, ecosystem resilience has been related to diversity (Tilman et al 2006), providing a link between diversity, enhanced ecosystem functioning and community resistance (and thus stability) against environmental changes.…”
Section: Theoretical Advantagesmentioning
confidence: 99%
“…However, community stability in structure and richness over time has been reported for various regions, extents, time periods, and taxa, despite changes in composition (Brown et al 2001;Sax 2002), human induced impacts, or strong climate changes, even during glacial periods (Rodríguez 2004). Current evidence indicates that some of the many processes modifying biodiversity spatial distribution may remain relatively constant regardless of environmental variations.…”
Section: Detection Of Evolutionarily Important Areas Speciesmentioning
confidence: 99%